Creating a “Market for Inventions”: A Referee Model - Gesualdo Grimaldi (Journal of Technology Management & Innovation, 2008)
This article considers that the flow of new not patented innovations is difficult to occur among firms, especially when some inventions are caused by serendipity. Here I develop a model to analyze the conditions for a “market for inventions” to exist. With the help of game theory in particular, I show that the creation of such a market is quite unlikely because unfair buyer’s behaviour and the possibility of expropriation of the new innovation renders the seller reluctant to negotiate with a potential buyer. So I argue for a solution that involves a third referenced party into the negotiation so that it can guarantee the flow of ideas among institutions and generate a surplus for the whole society.